Primary Leiomyosarcoma of the Male Breast: A Case Report - Yazan Masannat; Haytham Sumrien; Yousef Sharaiha (Case Reports in Medicine)
Primary leiomyosarcoma of the breast is a rare tumour with only around thirty cases reported in the literature. Most of the cases reported are in females, while only a few are reported in males. We present a case of primary breast leiomyosarcoma in a 59-year-old man that presented with a subareolar lump which felt to be benign clinically and radiologically but proven to be a leiomyosarcoma on excision.